Regulation by Selective Enforcement: The SEC and Initial Coin Offerings - James J. Park; Howard H. Park (Washington University Journal of Law & Policy, 2020)
The Securities and Exchange Commission regulates the securities markets. However, Initial Coin Offerings (ICOs) do not require the usual disclosure to the Securities and Exchange Commission when securities are sold to the public. Prior to ICOs, courts typically used the Supreme Court’s Howeytest to determine whether an investment is a security. The vagueness of this test resulted in the Securities and Exchange Commission using Regulation by Selective Enforcement. In selecting significant actions, the Securities and Exchange Commission has been able to publicize cases with facts favorable to treating ICOs as securities. Regulation by Selective Enforcement has successfully established the Security and Exchange Commission’s authority over ICOs. However, major legal issues still remain and by only sanctioning more recent ICOs, the early movers retain power. This Article concludes that although the Security and Exchange Commission has taken steps to regulate ICOs, it has yet to totally resolve when a token is a security.
Keywords: fintech; financial; financial services; financial technology; finance; finance law; law; technology law; securities regulation; sec reg; SEC